2013
DOI: 10.1038/labinvest.2012.180
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization of brain metastasis by targeting c-MET

Abstract: Radiotherapy is the most widely used therapeutic modality in brain metastasis; however, it only provides palliation due to inevitable tumor recurrence. Resistance of tumor cells to ionizing radiation is a major cause of treatment failure. A critical unmet need in oncology is to develop rationale driven approaches that can enhance the efficacy of radiotherapy against metastatic tumor. Utilizing in vivo orthotopic primary tumor and brain metastasis models that recapitulate clinical situation of the patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…One mechanism by which foretinib enhanced radiosensitivity was related to changes in DNA damage repair following irradiation 32. DNA repair following double-stranded DNA breaks requires a variant histone protein called H2A.X.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which foretinib enhanced radiosensitivity was related to changes in DNA damage repair following irradiation 32. DNA repair following double-stranded DNA breaks requires a variant histone protein called H2A.X.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Met protein expression and ligand-independent activation rose after ionising radiation, and silencing of MET led to increased radiosensitivity [1, 2, 14]. Therefore, in the present study, it was hypothesised that the HGF/Met axis drives radioresistance in breast cancer patients, and it was aimed to determine MET and HGF gene copy number, Met/HGF expression, and Met phosphorylation in breast tumours of patients randomised to receive either chemo- or radiotherapy, in order to study correlations with clinicopathological parameters and response to radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to EGFR, we have recently demonstrated that inhibition failed to induce significant cell death or robust radiosensitization in the cell lines used in this study. Although MET inhibition induces radiosensitization in other entities, it also failed to do so in our HNSCC cells pretreated for 2 hours with 2 different MET inhibitors. Additionally, effects of crizotinib or SU11274 on proliferation and cell survival without irradiation turned out to be very limited in the sub‐micromolar range, the concentration range where maximal MET inhibition was already achievable at the protein level (see Figure ).…”
Section: Discussionmentioning
confidence: 71%